Principles of teaching - Chand, Tara. (New Delhi : Anmol publication., 1999)
There Have Been Great Advances In The Field Of Educational Psychology In The Post World War Ii Period. Various Theories About Intelligence And Human Behaviour Have Been Propagated And Advanced By Various Psychologists And Educational Thinkers.This Book Tries To Help The Prospective Teachers To Comprehend Child Behaviour With The Help Of The Knowledge Of These Theories For Improving Teaching Skill. The Book Will Prove Of Immense Help To Prospective Teachers. Practical Exercises Have Been Given At The End Of Most Of The Chapters. It Is A Unique Combination Of Theory And Practice In The Principles Of Teaching.
Keywords: Teaching